REMODELING OF THE WALL OF THE ASCENDING COLON IN RATS UNDER THE INFLUENCE OF THE FOOD ADDITIVES COMPLEX - Kinash, O.V.; Yeroshenko, G.A.; Shevchenko, K.V.; Grygorenko, A.S.; Layosh, N.V.; Vatsenko, A.V.; Solod, A.V. (World of Medicine and Biology, 2023)
Food additives are substances added to raw materials, finished products and medicines to extend the shelf life of the product, prevent the development of pathogenic microflora, and improve taste and organoleptic qualities. Monosodium glutamate, sodium nitrite and ponceau 4R are among the most widely used food additives. The experiment involved 84 mature male rats. The animals received 0.6 mg/kg sodium nitrite E250, 20 mg/kg monosodium glutamate E621 and 5 mg/kg ponceau 4R orally. Samples of the ascending colon of rats for histological examination were taken at 1, 4, 8, 12 and 16 weeks. It was found that oral administration of the food additives complex MSG, ponceau 4R and sodium nitrite for 16 weeks causes significant changes in the morphometric parameters of the wall of the ascending colon in rats. A pronounced reaction of the intestinal mucosa is characterized by the destruction of intestinal epithelial cells and disruption of the crypt structure with subsequent incomplete recovery at late follow-up.